2017
DOI: 10.1016/j.archger.2017.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Concern about developing Alzheimer's disease or dementia and intention to be screened: An analysis of national survey data

Abstract: Objective Early diagnosis of Alzheimer’s disease (AD) or dementia is important so that patients can express treatment preferences, subsequently allowing caregivers to make decisions consistent with their wishes. This study explored the relationship between people’s concern about developing AD/dementia, likelihood to be screened/tested, if experiencing changes in cognitive status or functioning, and concerns about sharing the diagnostic information with others. Method A descriptive study was conducted using P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 33 publications
4
24
0
1
Order By: Relevance
“…Previous studies reported that a perceived high risk of AD and family history of cognitive disorders might motivate individuals towards enrolling in hypothetical AD drug trials [38,39] and increase willingness to undergo genetic or diagnostic assessments [26,[40][41][42][43]. Lawrence and colleagues observed that diagnostic confirmation was an important incentive for participation among cognitively impaired older adults [40].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that a perceived high risk of AD and family history of cognitive disorders might motivate individuals towards enrolling in hypothetical AD drug trials [38,39] and increase willingness to undergo genetic or diagnostic assessments [26,[40][41][42][43]. Lawrence and colleagues observed that diagnostic confirmation was an important incentive for participation among cognitively impaired older adults [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, it can be very difficult to encourage people to make lifestyle changes for a disease that may be decades away and especially when the causes of dementia are not yet fully understood. A recent national survey conducted in the USA on individual perceptions of health conditions [21], in a sample of 4,033 respondents, found that cancer ranked as the most feared condition (40.3%) compared to dementia (17.5%). However, recent changes in the leading cause of death stating that dementia has overtaken cancer and cardiovascular disease, may change these perceptions in the future [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…This differentiation is important as dementia may be under-screened and underdiagnosed ( 48 50 ). Indeed, a 2009 study estimated dementia was underdiagnosed in 50% of primary care patients aged 65 and above ( 48 ).…”
Section: Discussionmentioning
confidence: 99%